Síntese e caracterização de novos complexos de maleatos de íons lantanídeos trivalentes (La3+, Ce3+, Pr3+, Nd3+, Sm3+, Tb3+ e Er3+) - Costa, Bruna de Araújo (2020)
New complexes of lanthanides maleates were synthesized by the stoichiometric reaction between maleic acid and lanthanides hydroxycarbonates. The complexes were evaluated by a variety of techniques such as thermogravimetry and derivative thermogravimetry (TGA/DTG), differential scanning calorimetry (DSC), simultaneous TGA-DSC, DSC photovisual (microscope coupled to DSC), Fourier transform infrared spectroscopy (FTIR), evolved gas analysis (EGA) using TGA-FTIR and power x-ray powder diffraction (PXRD). The results of the analysis of these compounds provide information related to the such as stoichiometry, thermal stability, degree of hydration, hydration enthalpies, the main evolved gases during pyrolysis, the coordination mode between metal and ligand and the PXRD results. This detailed study intends to contribute to the area of synthesis of lanthanide compounds, motivating the elaboration of other syntheses, survey of more properties of these compounds or future applications with different functionalities.